Faktor Keuangan, Karakteristik Perusahaan dan Pengungkapan Corporate Social Responsibility - Damayanti, Nyoman Padmi; Krisna Dewi, Luh Gede (E-Jurnal Akuntansi; Vol 32 No 8 (2022)DO - 10.24843/EJA.2022.v32.i08.p02, 2022)
This study aims to empirically examine the effect of financial factors consisting of profitability, leverage, and market capitalization as well as characteristic factors consisting of company age, company size, and company profile on the disclosure of Corporate Social Responsibility (CSR). The study was conducted on state-owned companies listed on the Indonesia Stock Exchange for the period 2016-2020. The population in the study amounted to 25 state-owned companies. Sampling using purposive sampling technique as many as 18 companies that meet the criteria. Analysis of research data using multiple linear regression analysis. The results showed that profitability, leverage, market capitalization, company age, and company size did not affect the disclosure of Corporate Social Responsibility, while the company profile had a positive effect on the disclosure of Corporate Social Responsibility. This research can theoretically confirm the use of stakeholder theory and legitimacy theory. Keywords: Profitability; Market Capitalization; Company Age; Company profile; Corporate Social Responsibility.